Casa Experimental: Projecto e Memória - José Pedro Ribeiro de Oliveira Guedes (2020)
This is the memory of a project. An experimental project in Vila Nova de Gaia (Portugal) gives voice to a set of ideas, concerns and standpoints - developed throughout the learning of architecture - giving rise to a pre-existing dwelling - the subject matter of the present dissertation. The dissertation begins by presenting, through rigorous representations and three-dimensional objects, the status of the case study. This is a case that expresses itself as an unfinished product - were it not an attempt to shape the intrinsic faculties of the author - that, like knowledge, is an act of progressive learning, continuous updating and inconstant definition. It is followed by showing two aspects of a methodological discussion. A set of fragments is presented in a logical sequence - proving to be a frequent exercise throughout the development process of the project - manifesting themselves in the form of written thoughts. Whether in moments of enormous clarity or unprecise circumstances, they gather a set of readings and references that seek to contextualize and elucidate the reader on the image created by the author for the development of the proposed conception. A set of dense, intense images is presented - selected from the more academic means of production - capable of portraying a chronological order of the evolutionary process which, amid advances, setbacks, waivers and options, reveals the complexity of the project. A journey between theoretical and practical realities is suggested, understanding that both are inter-dependent and never pertinent as isolated elements. Additionally, a less unanimous format is proposed which explores the graphic aspect of an editorial document that presents a practical project, freeing it from the formal impositions of a particularly theoretical investigation, enhancing its experimental genesis. It is a cycle of studies that ends the same way it started: experimenting.